Modeling Of Enterprise Information System Architecture Planning In Private Universities In Indonesia - Kurnaedi, Didi (Proceedings of the Informatics Conference, 2020)
In strategic planning SI / IT is needed an enterprise architecture (EA) in order to achieve the alignment of SI / IT strategy with the business strategy of the organization. EA is seen as a logical, comprehensive, and holistic approach to define, design and implement system systems and components simultaneously. Data collection by interview, documentation, questionnaire, and direct observation of organization. The analysis used Value Chain, SWOT, PEST, Porters Five Force, and Critical Success Factor (CSF) method is a complete method orframework in designing an architectural enterprise, but it is necessary to understand each step in the methodology so that it can Translated and adapted for the needs of the organization. The expected result of this study is a form or formula for SI / IT strategic planning that is adapted to the business processes and requirements of the private University in Indonesia in designing the architectural enterprise for SI / IT strategic planning.